Methods, Techniques and Policies for Mobility in the Friendly City - Busi, Roberto (TeMA - Journal of Land Use, Mobility and Environment, 2011)
The environmental subject, as well known, greatly affects the planning and management of land and city. If probably it is incorrect and dangerous to deal with “sustainable development” (for the expectations that this expression produces as regards the real compatibility of the uses of development with the observance of environmental standards), in any case there should always be cultural behaviors and operating practices having respect for environment. The concept of “friendly city” is valuable because it contains also the demand for a reasonable behavior in relation to resources. The theme is strictly combined with the subject of mobility, for which, if it is faced with adequate models, there are already effective methods, techniques and policies available. There are several and complex urban and land planning applications of mobility. It is enough to consider the ones (a great deal!) directly connected with demand and supply of passengers and goods travel; the ones related to the important mechanisms of functions localization and their interrelation; the environmental ones produced by people and goods transport as well as by the allocation and deriving cause/effect comparisons; the landscape ones issuing from the physical intrusion of means of transport and the consequent perceptive effects. It is, indeed, in the relationships with environment and landscape that the question of mobility shows its great weight as factor of urban quality. Starting from the above premise, this paper describes an original author’s argument on some of the main issues faced by the supporters and detractors of the principle of sustainability, which leads to the new concept of friendly city. The said argument, based on the integration among land, mobility and environment, is consciously addressed to highlight the fundamental elements for the re-establishment of the urban, land planning and transportation disciplines as well as to lead the urban quality of life to levels no attainable otherwise. The first part of the paper deals with the conceptual correctness of the principle of sustainability and its applications. The second part investigates the most consistent and reasonable modalities of travel, such as the pedestrian one, reaffirming that the modern city has failed whenever it has been planned for the individual vehicle mobility. The third part aims at briefly defining the actions of an innovating approach to mobility in urban field. The fourth part, finally, points out the operating and practical consequences.